mTOF performance during the first main commissioning beam time at mCBM - Zhang, Qiunan; Deppner, Ingo Martin; Herrmann, Norbert; Wang, Y. (Journal of Instrumentation, 2020)
The future Facility for Anti-proton and Ion Research (FAIR), currently in construction in Darmstadt, Germany, is one of the largest research projects worldwide. The Compressed Baryonic Matter (CBM) experiment is one of the main pillars at FAIR, studying the quantum chromodynamics (QCD) phase diagram at high baryon densities with unprecedented interaction rate in heavy ion collisions up to 10 MHz. This requires new data-driven readout chain, new data analysis methods and high-rate capable detector systems. The task of the CBM Time-of-Flight wall (CBM-TOF) is the charged particle identification. Multi-gap Resistive Plate Chambers (MRPCs) with different rate capabilities will be used at CBM-TOF corresponding regions. To reduce the commissioning time for CBM, a CBM full system test-setup called mini-CBM (mCBM) had been installed and tested with beams at GSI SIS18 facility in March 2019, which was the first main commissioning beam time at mCBM. These tests were not only system tests to make preparations for CBM but also commissioning runs for mCBM which finally aims at measuring Lambda baryon production with high rate up to 10 MHz. High-rate MRPC prototypes equipped with low resistive glass called MRPC2, were selected to be implemented in mTOF modules for mCBM. The first test results of MRPC2 and the mTOF system will be shown.